Pregnancy-related pelvic vein thrombosis - S. Schulman (Акушерство, гинекология и репродукция)
Pregnancy is a hypercoagulable state due to pro-hemostatic changes in the activity of coagulation factors and fibrinolysis and due to progressively increasing pressure on the iliac veins from the growing uterus. Thus, it is not surprising that there is an increased risk for thrombotic events and especially in the pelvic veins. With the trauma of delivery, and particularly caesarian section, the risk is accentuated in the early days postpartum. Multiparity seems to be another risk factor, which may be due to the older age of the patient. The epidemiology, risk factors, diagnosis, management and prognosis of iliac, ovarian and uterine vein thrombosis will be reviewed here, with emphasis on the relation to pregnancy.